Trends and dynamics of inequality in Alberta. (3rd July 2018) - Al-Zyoud, Hussein; Islam, Shahidul; Leblanc, Carolyn
ABSTRACT: The gender wage gap has been a subject of conversation for decades. Over the past 30 years, many authors have examined the gender wage gap and income inequality in Canada, but few have investigated the unique circumstances which impact the various regions of the nation. Using the Canadian Labour Force Survey data for the period 1976–2004, this study examines the trends in earnings of males and females in Alberta, Canada by investigating the impact of differences in productivity, education, age, and industry on the gender wage gap. Previous literature suggests that differences in labour force participation rate, education level, skill achievement, age, and type of industry are the key variables for explaining gender income differences in employment. These variables are investigated using a linear regression to determine impact on the gender wage gap. Results suggest that the gender wage gap increases due to differing productivity levels and increases in relation to changes in employment participation of females aged 25–44 years. Two interesting results were identified from the data of this study. Specifically, an increase of women in the goods producing industry reduced the gender wage gap for that population; while, an increase of women in the service industry resulted in an increase of the gender wage gap. These findings are significant for understanding how legislation regarding wage, work week, and social benefits impact the gender wage gap.